Until we reach home eaudiobook - Austin, Lynn (Recorded Books Inc., 2014)
A Christy Award WinnerOnly in crossing a seemingly endless ocean will they find the true meaning of love, faith, and homeLife in Sweden feels like an endless winter to Elin Carlson after the deaths of her parents. When circumstances become unbearable, she determines to find a safe haven for her sisters.So begins their journey to America ... the land of dreams and second chances.But as hardship becomes their constant companion, Elin, Kirsten, and Sofia question their decision to immigrate to Chicago. Will their hopes for the future ever be realized?